Märkte als konkrete Handlungssysteme: Einige Überlegungen zur Korruption in Italien. - Magatti, Mauro (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2003)
In the eighties in Italy emerged a system of corruption, which transcended the classical figure of reciprocity between persons who know each other very well. Corruption was expected in certain situations from all sides and so it could work even between persons, who didn’t know each other. This system of corruption fit very well in the market system. It was not a deviation, but a constitutive moment of Italian capitalism in the eighties, which allowed simple solutions for problems hard to solve in a democratic system.